2018
DOI: 10.1136/openhrt-2018-000801
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of medium-term mortality in patients hospitalised with coronary artery disease in a resource-limited South-East Asian setting

Abstract: ObjectiveTo measure medium-term outcomes and determine the predictors of mortality in patients with coronary artery disease (CAD) both during and after hospitalisation in a resource-limited South-East Asian setting.MethodsFrom February 2013 to December 2014, we conducted a prospective observational cohort study of 477 patients admitted to Makassar Cardiac Center, Indonesia, with acute coronary syndrome and stable CAD. We actively obtained data on clinical outcomes and after-discharge management until April 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
7
2
3
Order By: Relevance
“…In the study setting, the delayed initiation of invasive diagnostic and therapeutic options, coronary angiography started on February 2016 and PCI on April 2016, might explain the mortality rate. Similarly, another study from south east Asian setting reported that unavailability of revascularization therapy was associated with high mortality rate (HR; 2.38, p = 0.005) [46]. However, our finding was higher than studies from India 3.9% [22], Czech republic 4.2% [47], Brazil 9.4% [48], Pakistan 12.2% [49], Kenya 9.4% [30] and Sub-Saharan African countries 10% [10].…”
Section: Discussioncontrasting
confidence: 62%
“…In the study setting, the delayed initiation of invasive diagnostic and therapeutic options, coronary angiography started on February 2016 and PCI on April 2016, might explain the mortality rate. Similarly, another study from south east Asian setting reported that unavailability of revascularization therapy was associated with high mortality rate (HR; 2.38, p = 0.005) [46]. However, our finding was higher than studies from India 3.9% [22], Czech republic 4.2% [47], Brazil 9.4% [48], Pakistan 12.2% [49], Kenya 9.4% [30] and Sub-Saharan African countries 10% [10].…”
Section: Discussioncontrasting
confidence: 62%
“…distance ≥20 kms from hospital). In our previous study, all these variables are shown to be the independent predictors for mid-term all-cause mortality in patients with coronary artery disease in Indonesia 11 . We considered a 95% confidence interval not including one, with p-value < 0.05 as statistically significant.…”
Section: Methodsmentioning
confidence: 87%
“…We excluded all patients who immediately died in the emergency department or intensive cardiovascular care unit before giving informed consent, and all patients in whom coronary angiography had been confirmed as normal (defined as 0% lumen stenosis in all coronary vessels) 10 . Detailed description and flowchart of the study population has been previously reported 11 .…”
Section: Methodsmentioning
confidence: 99%
“…In A.Qanitha [16] which assess the Predictors of medium-term mortality in patients hospitalised with coronary artery disease, there was statistical significant difference regarding age and sex.…”
Section: Markers Of Acsmentioning
confidence: 98%